One-year outcomes following surgery for necrotising enterocolitis: a UK-wide cohort study - Allin, B; Long, A; Gupta, A; Lakhoo, K; Knight, M (BMJ Publishing Group, 2017)
Objective: The objective was to describe outcomes and investigate factors affecting prognosis at one-year post-intervention for infants with surgical NEC. Design: Utilising the British Association of Paediatric Surgeons Congenital Anomalies Surveillance System, we conducted a prospective, multi-centre cohort study of every infant reported to require surgical intervention for NEC in the UK and Ireland between 01/03/2013 and 28/02/2014. Association of independent variables with one-year mortality was investigated using multivariable logistic regression analysis. Setting: All 28 paediatric surgical centres in the UK and Ireland. Patients: Infants were eligible for inclusion if they were diagnosed with NEC and deemed to require surgical intervention, regardless of whether that intervention was delivered. Outcomes: Primary outcome was mortality within one-year of the decision to intervene surgically. Results: 236 infants were included in the study. 208(88%) had one-year follow-up. 59 of the 203 infants with known survival status(29%,95%CI 23%-36%) died within one year of the decision to intervene surgically. Following adjustment, key factors associated with reduced one-year mortality included older gestational age at birth(aOR0.87,95%CI 0.78-0.96). Being small for gestational age (SGA) (aOR3.6,95%CI 1.4-9.5), and requiring parenteral nutrition at 28-days post-decision to intervene surgically (aOR3.5,95%CI 1.1-11.03) were associated with increased one-year mortality. Conclusions: Parents of infants undergoing surgery for NEC should be counselled that there is approximately a 1:3 risk of death in the first post-operative year, but that the risk is lower for infants who are of greater gestational age at birth, who are not SGA, and who do not require parenteral nutrition at 28-days post-intervention.